New Medieval literatures 20 - Robertson, Kellie 1968-; Scase, Wendy 1955-; Ashe, Laura ca. 20./21. Jh; Knox, Philip 1988- (Boydell & Brewer, 2020)
New Medieval Literatures is an annual of work on medieval textual cultures, aiming to engage with intellectual and cultural pluralism in the Middle Ages and now. Its scope is inclusive of work across the theoretical, archival, philological, and historicist methodologies associated with medieval literary studies, and embraces the range of European cultures, capaciously defined. Essays in this volume investigate a range of writers from late antiquity to the fifteenth century. They explore encounters between humans and animals in French romance; reflect on what contemporary sound studies can offer to Anglo-French poetry; trace how the reception of Trojan history is influenced by late medieval military practices; attend to the complex multilingualism of a devotional poetry that tests the limits of both language and theology; analyse the ways in which Christ's sexuality upsets religious typology in late medieval drama; document the lines of national and European affinities found in French poetic manuscripts; and argue for why we should study "ugly" manuscripts of practical instruction not only for what they teach us but also for their insights into medieval literacy. Texts discussed include romances such as Chrétien de Troyes's Yvain and Béroul's Tristan; the theologian John of Howden's adaptation of the Philomela legend in his Rossignos; Chaucer's Troilus and Criseyde read alongside siege chronicles of the Hundred Years War; Bruder Hans's quadrilingual Ave Maria; the York Corpus Christi Plays; the poetry of Charles d'Orléans; and a group of late medieval manuscripts which include herbals, account books, and medical treatises